2007
DOI: 10.1590/s1413-86702007000200017
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a self-collection kit for the microbiological study of the vaginal content

Abstract: Diagnosis of vaginal discharge is frequently performed in an empirical way, leading to inadequate treatment. This study tested the accuracy of a self-collection kit for microbiological study of the vaginal content. One hundred and forty-two women of Family Health Program units in Niterói and Piraí cities were enrolled in order to have their vaginal content studied. A brief explanation and a self-collection kit were provided in order to sample the vaginal content. The self-collection kit was composed of one emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…Unexpectedly, the BV rate in the present study was not only lower than in pregnant women attending a Primary Care Service [28] or an outpatient service specialized in infections in Obstetrics [6] in the same region, but was also lower than in non-pregnant Brazilian [29] and North-American women [24]. This low Total of patients may vary among the categories as some of the data was unavailable prevalence of bacterial vaginosis could partly be explained by the consideration that combined infection of vaginal candidosis and BV was analyzed separately from BV without co-infection.…”
Section: Discussioncontrasting
confidence: 55%
“…Unexpectedly, the BV rate in the present study was not only lower than in pregnant women attending a Primary Care Service [28] or an outpatient service specialized in infections in Obstetrics [6] in the same region, but was also lower than in non-pregnant Brazilian [29] and North-American women [24]. This low Total of patients may vary among the categories as some of the data was unavailable prevalence of bacterial vaginosis could partly be explained by the consideration that combined infection of vaginal candidosis and BV was analyzed separately from BV without co-infection.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies have shown that patients are in general satisfied with self-sampling [7Y9]. It is easy to perform, can be done in full privacy, and is well accepted [7,8,10]. None of our patients reported complaints pertaining to the vaginal self-sampling procedure.…”
Section: Discussionmentioning
confidence: 68%
“…In such cases, it may be worthwhile to provide patients with a set of swabs (with or without transport medium) for self-sampling at times of increased complaints, to be sent by regular post to the lab directly. This technique has been proven fruitful to pick up at least another 30% of positive patients that otherwise would have remained undiagnosed and most likely erroneously treated for other nonexisting diseases [17,18] . On the other hand, as lowering the load of infection leading to reduced symptoms are the main stay of suppressive therapy, the use of cultures in the absence of symptoms can be discussed.…”
Section: Culture Techniquesmentioning
confidence: 99%